Synthesis and Characterization of Film-forming Polymer/SiO2 Nanocomposite via Surfactant-Free Emulsion Polymerization - Shang, Qianqian; Liu, Hu; Gao, Lijing; Xiao, Guomin (Asian Journal of Chemistry, 2013)
Poly(methyl methacrylate-co-butyl acrylate-co-methacrylic acid)/SiO2 (PMMA-BA-MAA)/SiO2) nanocomposite particles were prepared via surfactant-free emulsion polymerization. The effects of SiO2 content on the emulsion stability, monomer conversion and polymerization rate were investigated. The experimental results revealed that (PMMA-BA-MAA)/SiO2 nanocomposite particles were film-forming and the polymer spheres with ordered arrangement structure were bounded by SiO2 networks. SiO2 particles (or aggregates), which had strong interaction with the polymer matrix, were enriched at the surface of the nanocomposite films. The dried nanocomposite films showed better water resistance than the pure polymer film and the film containing 10 wt % SiO2 had the lowest water adsorption (0.070 g/g).